Digitization of Village Government as a Sustainable Development Strategy Towards the Realization of Smart Villages - Geohansa, Ahmad; Sumarna, Eeng; Kania, Ikeu (Jurnal Polisci, 2025)
Background. Digital transformation in rural government organizations is key to increasing the effectiveness of governance, transparency, and community participation in village development. The Smart Village concept presents an innovative approach integrating digital technology in public administration, community services, and village economic empowerment. The Indonesian government has established various policies, such as Law Number 6 of 2014 on Villages and the Digital Village program, to encourage the modernization of village government. However, its implementation is still faced with various challenges, such as the limitation of technological infrastructure, the readiness of human resources in village government organizations, and the lack of optimal policy synchronization at the central and regional levels. Aims. Therefore, this study aims to explore how digitalization can strengthen village governance, identify supporting and inhibiting factors in implementing Smart Villages, and formulate policy strategies that can accelerate digital transformation in sustainable village development. Methods. This research uses a qualitative approach with document analysis, obtaining data from various secondary sources, including the Citengah Village Medium-Term Development Plan (RPJMDes) 2019-2024, village digitalization policies, and relevant academic literature. Result. The study results show that Citengah Village has initiated various digitalization programs, such as implementing an electronic-based administrative system and optimizing the village information system. However, the document study revealed that the implementation of Smart Village still experienced obstacles in village government organizations' capacity to manage digital systems, budget limitations, and weak cross-sector coordination in the development of digital infrastructure. From the perspective of sustainable development, digitalization in village government organizations has not fully supported digital-based economic empowerment, increased public service efficiency, and optimized technology use in village resource management. Conclusion. This research is unique in linking the concept of Smart Villages with strengthening village government organizations in the context of sustainable development, which distinguishes it from previous studies that focused more on technological aspects without considering village institutional dynamics. The document analysis-based approach also provides a more systematic policy-based evaluation, allowing for secondary data-driven studies without relying on subjective opinions. Implementation. This research is also expected to produce an organizational and contextual village digitalization strategy model, which can be used as a reference in formulating policies to increase the effectiveness of technology-based village government. Therefore, although village digitalization has great potential in improving the quality of public services and village economic competitiveness, its success is highly dependent on the readiness of village government organizations, strengthening the capacity of human resources, and harmonizing digitalization policies at the national and regional levels.